SERUM PROTEIN PROFILE AS A BIOMARKER IN DIAGNOSING LEISHMANIOSIS AND MONOCYTIC EHRLICHIOSIS IN DOGS - SANTOS, M. P. F.; PAIFFER, F.; VIROEL, F. J. M.; TEIXEIRA, R. H. F.; GOMES, A. H. S.; SILVA, W. T.; OLIVEIRA, T. M. F. S.; NAKAGHI, A. C. H. (Ars Veterinaria, 2021)
Diagnosing Canine Visceral Leishmaniosis is challenging for veterinarians given that its hematological and biochemical abnormalities greatly resemble those of other illnesses of dogs, such as canine ehrlichiosis, which is caused by Ehrlichia canis and is highly prevalent with high pathogenicity. The aim of this study was to determine occurrences of serological positivity for the antigens of Ehrlichia canis and Leishmania infantum and its relationship to globulin concentrations in samples from dogs. Out of 93 samples tested, 12.9% were negative for the antigens of both L. infantum and E. canis; 33.3% were seropositive for both antigens. Discordant results were found from 18.3% that were positive only for L. infantum, while 35.5% were positive only for E. canis. Hyperglobulinemia was observed in 88.2% and the statistical analysis showed that there was a significant relationship between the high levels of globulins and seropositivity for the antigen of E. canis. However, the relationship between positivity for the antigen of L. infantum and hyperglobulinemia, showed that there was no statistically significant relationship between the two laboratory findings. From these results, it can be concluded that concomitant infections occur frequently and that hyperglobulinemia is more closely related to ehrlichiosis than to leishmaniosis, in dogs.